Pengaruh Konsumsi Air Kelapa Hijau Dalam Penurunan Intensitas Dismenore Di Sumatera Selatan - Sumantri; Kurnia Sari (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2023)
Background: Dysmenorrhea in adolescents usually occurs due to very high prostaglandinhormones on the first day of menstruation. Dysmenorrhea affects productivity such as disruption oflearning activities causing a lack of focus in lessons and can even increase absenteeism fromschool. One effort that can be done to relieve dysmenorrhea is non-pharmacological therapy ofgreen coconut water. Green coconut water contains vitamins and minerals that can stimulate thebody to stabilize the prostaglandin hormone so that dysmenorrhea pain decreases.Research Objectives: This study aims to determine the effect of consuming green coconut water(Cocos Nucifera Linn Var. Viridis) on reducing the intensity of dysmenorrhea in young women inSungai Pinang 1 Village, Ogan Ilir District, South Sumatra.Research Methods: The type of research used is a quantitative research with a quasi-experimentaldesign with a one group pretest and posttest serial design. Total sampling data collectiontechnique obtained. The data analysis used non-parametric statistics because the data were notnormally distributed, the Wilcoxon test was used with a significant level of 0.05. Results: there was a decrease in the intensity of pain response before treatment pain score 128with a mean score of 4.74 (moderate pain) after treatment I, II and III there was a decrease in painscore 72 with a mean score of 2.77 (mild pain). Green coconut water has a significant effect onreducing the intensity of dysmenorrhea with a significant level of p 0.000 Z score -4.633 (Z scoretable = 107).Conclusion: There is a significant effect on reducing the intensity of dysmenorrhea after consuminggreen coconut water in young women in Sungai Pinang 1 Village, Ogan Ilir District.Keywords: Green coconut water, dysmenorrhea, pain intensity